1967
DOI: 10.1128/jvi.1.4.758-770.1967
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recombination in T4 Bacteriophage Deoxyribonucleic Acid I. Tertiary Structure of Early Replicative and Recombining Deoxyribonucleic Acid

Abstract: A replicative hybrid resulting from the infection of heavy (substituted with 5bromodeoxyuridine) bacteria with light (not substituted with 5-bromodeoxyuridine) radioactive bacteriophage was isolated from a CsCI density gradient. Sedimentation studies indicate that 60% of the deoxyribonucleic acid (DNA) behaves as if it were in units more than four times as large as an intact reference molecule. Under the electron microscope, hybrid molecules appeared tangled, showed puffs and loops, occupied a small area, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1967
1967
1982
1982

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…As with the wild-type phage (10), the integrity of the strands of DNA from DNA-deficient amber mutants is affected after infection of a nonpermissive host. This breakage of polynucleotide chains can be inhibited by CM, which implies that a new enzyme is required for this breakage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with the wild-type phage (10), the integrity of the strands of DNA from DNA-deficient amber mutants is affected after infection of a nonpermissive host. This breakage of polynucleotide chains can be inhibited by CM, which implies that a new enzyme is required for this breakage.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for analysis in alkaline sucrose gradients have also been described (10), as have the details of using CM (11). Extraction of native intracellular DNA was by the sodium dodecyl sulfate-Pronase-1193 on July 6, 2020 by guest http://jvi.asm.org/ Downloaded from KOZINSKI AND FELGENHAUER phenol (SPP) method (12), which is similar to the method of Berns and Thomas (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since chloramphenicol is known to inhibit protein synthesis, it was concluded that the T 4 DNA coded for an enzyme necessary for recombination which cut the DNA, and that the production of this enzyme was being inhibited. Kozinski, Kozinski & James (1967) applied chloramphenicol at different times after infection, and found there was a gradient of inhibition of (u) DNA synthesis, (b) cutting of single chains and (c) repairing activities, in that order. They concluded that the enzyme responsible for cutting single chains in duplex DNA was coded by T 4 and was required for recombination.…”
Section: (B) Recombination-deficient Mutantsmentioning
confidence: 99%
“…In the experiments which follow, we will attempt to demonstrate the genetic nature of the pulse-labeled progeny DNA synthesized at late times after the onset of DNA replication under two conditions: when the covalent addition of progeny DNA to recombinant intersections is inhibited, and when there is covalent joining. It should be recalled here that in the past we have demonstrated that timely addition of CM serves as a fine dissecting tool, separating various replicative events (16). When CM is added at 5 to 6 min past infection there is no parent-toprogeny recombination, and the newly synthesized progeny DNA displays a genetic bias, being fixed in the amplifying mode (18).…”
mentioning
confidence: 93%